In-service training and its relationship to psychological hardiness among teachers of students with special needs in the integration classes in the northern governorates of Palestine - Hamdan, Dr Salah Al-Din Hassan Mustafa; Oteer, Dr Rabee Shafiq Lutif (IJRDO- Journal of Educational Research, 2017)
The current study aimed to identify in-service teacher training and its relationship topsychological hardiness among special education teachers in the integration classes inthe Tulkarm Governorate. The sample of the study consisted of 70 special educationteachers who worked in the Tulkarm Directorate of Education. The two researchersused the study tool of in-service training (IST) as well as the Psychological HardinessScale. The results of the study revealed that score of in-service training was very high,and that score of the psychological hardiness was also very high. In addition, therewas a direct correlation between in-service training and the psychological hardiness,i.e. the in-service training increased the psychological hardiness. There were yet nostatistically significant differences due to the variables of gender and years ofexperience. On other hand, there were significant differences due to the variable ofeducational qualification in favor of the holders of the bachelor degrees or below. Thestudy recommended the need to develop a comprehensive plan for teachers so thatthey could effectively deal with students with special needs in public schools, and theneed to provide them with an intensive in-service training for special education.